An Inertia Driven Micro‐Actuator for Space Applications. Issue 3 (March 2014) - Mita, Makoto; Ataka, Manabu; Fujita, Hiroyuki; Toshiyoshi, Hiroshi
SUMMARY We have developed an inertia‐driven micro actuator for the harsh environment of space. Different from the conventional PZT‐driven or other actuators, the newly developed electrostatic mechanism is free from material property change due to temperature. A mass suspended in the actuation system is designed to collide with the internal wall to produce thrust by an impact‐type inchworm mechanism.